Cytotoxic Prenylated Xanthones from the Leaves of Garcinia bracteata - Zhang, Bao-Jun; Fu, Wen-Wei; Wu, Rong; Yang, Jin-Ling; Yao, Cai-Yun; Yan, Bing-Xiong; Tan, Hong-Sheng; Zheng, Chang-Wu; Song, Zhi-Jun; Xu, Hong-Xi (Planta Medica, 2019)
Six new prenylated xanthones (1–6) and seventeen known xanthones were isolated from extracts of Garcinia bracteata leaves. Their structures were determined by extensive NMR and MS spectroscopic data analysis. The inhibitory activities of the isolates were assayed on HeLa, A549, PC-3, HT-29, and WPMY-1 cell lines. Compounds 1 and 15–17 showed moderate inhibitory effects on tumor cell growth, with IC50s ranging from 3.7 to 14.7 µM.
Keywords: Garcinia bracteata; Clusiaceae; prenylated xanthones; cytotoxicity